Expectation of Poisson Distribution/Proof 1
Jump to navigation
Jump to search
Theorem
Let $X$ be a discrete random variable with the Poisson distribution with parameter $\lambda$.
Then the expectation of $X$ is given by:
- $\expect X = \lambda$
Proof
From the definition of expectation:
- $\ds \expect X = \sum_{x \mathop \in \Img X} x \map \Pr {X = x}$
By definition of Poisson distribution:
- $\ds \expect X = \sum_{k \mathop \ge 0} k \frac 1 {k!} \lambda^k e^{-\lambda}$
Then:
\(\ds \expect X\) | \(=\) | \(\ds \lambda e^{-\lambda} \sum_{k \mathop \ge 1} \frac 1 {\paren {k - 1}!} \lambda^{k-1}\) | as the $k = 0$ term vanishes | |||||||||||
\(\ds \) | \(=\) | \(\ds \lambda e^{-\lambda} \sum_{j \mathop \ge 0} \frac {\lambda^j} {j!}\) | putting $j = k - 1$ | |||||||||||
\(\ds \) | \(=\) | \(\ds \lambda e^{-\lambda} e^{\lambda}\) | Taylor Series Expansion for Exponential Function | |||||||||||
\(\ds \) | \(=\) | \(\ds \lambda\) |
$\blacksquare$